"Słyszałam jak pisało pióro po papierze". Wspomnienia z domu Henryka Sienkiewicza = "I have heard the pen writing on the paper". Memories from Sienkiewicz's home - Kuniczuk-Trzcinowicz, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the article there were used fragments of housekeeper's and maid's memories employed by Henryk Sienkiewicz. The story - preserved in the archives of Polish Radio - shows daily routine of a Polish writer. So we get to know the author of "Quo Vadis" through the memories of people who had direct and often long-term contact with him. It extends the context for exploring the notions and interpretation of the Sienkiewicz's works. The article also uses the writer's correspondence and other written sources, broadening the circumstances of knowledge about Sienkiewicz - as an individual and public figure.
Keywords: Sienkiewicz, Henryk (1846-1916); Oblęgorek; wspomnienia; codzienność; memories; daily existence